IS THE PATIENT PARTNERSHIP INFORMATIVE IN PHARMACOVIGILANCE? - Yu. V. Muravyev (Научно-практическая ревматология, 2017)
The paper discusses whether patients' spontaneous reporting on adverse drug reactions is appropriate and possible.